The Effect Of Using Quizlet Application In Learning English Vocabulary: An Experimental Study At Vii Grade Students of SMPN 3 Praya Tengah - Pratiwi, Siti Nurpadila; Arafiq; Putera, Lalu Jaswadi; Melani, Boniesta Zulandha (Journal of Authentic Research, 2025)
This quasi-experimental research examined the impact of the Quizlet application on students’ English vocabulary mastery at SMPN 3 Praya Tengah, a rural junior high school located in Central Lombok, Indonesia. The study was conducted in response to students’ limited vocabulary knowledge and the insufficient use of interactive digital learning tools. Thirty seventh-grade students participated and were assigned to experimental and control groups. A 30-item vocabulary test focusing on the topic “Personality and Skills” was administered as both pre-test and post-test. The experimental group underwent five instructional sessions utilizing Quizlet’s interactive modes Flashcards, Learn, Match, and Test while the control group received conventional instruction. The test instrument was validated by expert reviewers, and its reliability coefficient, measured through Cronbach’s Alpha, was 0.87, indicating high internal consistency. Data were processed using SPSS 26, including tests of normality, homogeneity, and an independent samples t-test. Statistical analysis revealed a significant difference between the two groups (t(28) = 3.57, p = 0.002, d = 0.80), resulting in the rejection of the null hypothesis (H?) and acceptance of the alternative hypothesis (H?). These findings demonstrate that Quizlet effectively enhances students’ vocabulary mastery, learning motivation, and autonomy. The results also align with retrieval practice and gamification theories, confirming that Quizlet can serve as an effective digital medium for improving vocabulary acquisition, especially in rural educational settings with limited access to technology This suggests Quizlet can be integrated into junior high school curricula to promote autonomous vocabulary acquisition.